EL HALLAZGO DE NUEVE SITIOS ARQUEOLÓGICOS CON QUILLCAS EN CAJACAY, BOLOGNESI - ANCASH - Dalen Luna, Pieter van (2017)
The upper basin of the Fortaleza river is a territory of abundant archaeological sites, many of which correspond to sites with cave paintings, mostly associated with chullpas funerary structures. This evidences the existence of a wide and long cultural rock tradition, where natural elements are represented in articulation with the man and his domestic activities.